Effects of fish culture on particulate organic matter in a reservoir-type river as revealed by absorption spectroscopy and fluorescence EEM-PARAFAC. (January 2020) - Wang, Hui; Wang, Yonghao; Zhuang, Wan-E; Chen, Wei; Shi, Weixin; Zhu, Zhuoyi; Yang, Liyang
Abstract: Dam construction and fish culture can change the biogeochemical processes in river, yet their impact on the spectral properties of particulate organic matter (POM) remains to be studied. This was investigated in a reservoir-type river (Minjiang river, SE China) using absorption spectroscopy and fluorescence excitation-emission matrices-parallel factor analysis (EEMs-PARAFAC). Five fluorescent components were identified from POM with PARAFAC. Four components C1–C4 were affected by the seasonal variations of rainfall and runoff, indicating the influences of hydrological condition and terrestrial inputs. The Chlorophyll a concentration (Chl a ) correlated significantly with the humic-like C3 ( p  < 0.05) and the protein-like C4 ( p  < 0.01), indicating phytoplankton was an important source of C3 and C4. The Chl a and fluorescence intensities of C3–C4 were higher in the fish culture zones than in other areas, and the absorption coefficient a 300 and C1–C4 were lower downstream the dam. These results indicated that fish farming in the reservoir probably promoted the production of POM. The a 300 and C1 per unit mass of suspended particulate matter ( a 300 /TSM and C1/TSM) correlated significantly with the median particle size ( p  < 0.01), which might be related to the contribution of micro-phytoplankton. The absorption spectra of POM showed a shoulder peak at ∼280 nm, and its intensity correlated significantly and positively with Chl a ( p  < 0.01). These results indicated that the peak was probably derived from phytoplankton production. Our results have implications for better understanding the influences of human activities on the dynamics of river POM. Graphical abstract: Image 1 Highlights: POM was affected by terrestrial input and phytoplankton production. Fish culture promoted the production of POM. PCA based on POM indices was capable of identifying the effects of fish culture. CPOM and C1 were enriched in larger particles. The absorption shoulder peak was associated with phytoplankton production.